Chemical Composition and Termiticidal Activity of Artemisia nilagirica Essential Oil Growing in Southern Hilly Regions of India. Issue 1 (2nd January 2017) - Mishra, Tripti; Srivastava, Manjoosha; Kumar, Anil; Pal, Mahesh; Tewari, S.K.
Abstract: Essential oil of Artemisia nilagirica isolated from aerial parts was analyzed for antitermite activity. Chemical constituents were identified by gas chromatography-mass spectroscopy. Total forty constituents have been identified which is 93.55 % of the essential oil. Major constituents of the oil were α-thujone (33.78 %), germacrene-D (9.31 %), β-thujone (6.01 %), caryophyllene (5.86 %), caryophyllene oxide (6.17 %), borneol (2.16 %). The essential oil consist of 41.34 % monoterpene hydrocarbon, 30.9 % sesquiterpene hydrocarbon, 10.24 % monoterpene alcohol, 8.33 % sesquiterpene oxide along with 2.74 % sesquiterpene alcohol. The essential oil exhibited significant antitermite activity against Microtermes beesoni the termite. ED50 for termite repellency was found 4.44 mg/g and 5.81 mg/g for termite mortality. Chlorpyriphos 20 % TC was taken as control, ED50 of chlorpyriphos was found 1.53 mg/g. This study indicated that A. nilagirica essential oil can be used as a wood preservative to control the termites infesting wooden material and commodities.